Developing an input-output model for benchmarking company resource usage - Rodrigues, Pedro Miguel Vicente Bila (2016)
The intensive exploitation of natural resources and the increased awareness regarding the impact of their consumption on the environment suggests the need to be more efficient and to encourage a sustainable use of these resources. This is also a major goal for all industrial companies that are currently facing high costs related to energy, water, and material resources for production while aiming to remain competitive in the market. This dissertation introduces the development of a model, which through data input proceeding from resource’s consumption in manufacturing companies generates an output of resource efficiency indicators in six different categories (materials, energy, water, wastewater, solid-waste; air-emissions) which are in turn used for benchmarking company resource usage and then provide a solid basis for decision-making regarding the implementation of resource efficiency measures, that shall lead companies to improve their overall efficiency and profitability. In order to further assess the companies’ performance in terms of resource efficiency, it is applied a ranking system using fuzzy logic due to its ability to model complex realities and use subjective information based on human knowledge and experience.